EDUCATIONAL TECHNOLOGY “FLIPPED CLASSROOM” IN TEACHING THE DISCIPLINE “THE RUSSIAN LANGUAGE AND THE CULTURE OF SPEECH” - E. V. Kalachinskaya (Высшее образование в России)
The article analyzes the experience of introducing blended learning at the university on the example of a discipline “The Russian Language and the Culture of Speech”. The prospects of a mixed form of training as the most important factor of the transition from passive learning to active are substantiated. The author dwells on the principles of the “flipped classroom” technology based on the rearrangement of the key components of the educational process with the active use of electronic educational environment. The paper shows the advantages of using the “flipped classroom” technology from the point of view of optimizing the audience load, students’ motivation, orientation at the effective formation of their general cultural competences. The author presents the new methodical approaches to designing the discipline “The Russian Language and the Culture of Speech” aimed at improving the quality of teaching.